Analysis of E-Commerce Based on Business Incubators as an Effort to Improve the Sports Industry for MBKM Partners' Entrepreneurial Activities - Tedi Kustandi; Fakhri Fajrin Kurniawan (SAFE-Network, 2023)
Based on observations made by researchers, it was found that 1) The current global era makes challenges and competition increasingly sharp in capturing market share so that companies are required to utilize their resources effectively and efficiently in order to have a competitive advantage, 2) In Indonesia, the results of a survey conducted BPS also shows that as many as 84.92% of business actors still do not use E-commerce for various reasons, 3) General problems faced by MSMEs in Indonesia in developing their businesses include a) limited funding for business development b) low quality of human resources c) low ability to produce innovative products and d) weak mentoring (incubation). The research objective is to examine business incubator-based e-commerce as an effort to improve the sports industry for the entrepreneurial activities of Merdeka Belajar Kampus Merdeka (MBKM) partners. The research method uses descriptive quantitative qualitative research methods with a survey approach. The subjects of this research are the sports industry business people in Cirebon who understand the concept of business incubators selected using a purposive sampling technique. The results of this research show that sports industry entrepreneurs in Cirebon with presentations (55%) have a high level of influence in improving the sports industry. The conclusion of this research is that the use of business incubator-based e-commerce to improve the sports industry can give rise to new entrepreneurs who participate in developing the business of sports industry entrepreneurs in Cirebon, and the target of increasing the economic growth of the sports industry in the entrepreneurial activities of MBKM partners is achieved.